2011
DOI: 10.1039/c1cc14261e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dispersion and durability of Pt nanoparticles on a thiolated CNT support

Abstract: High dispersion Pt nanoparticles supported on surface thiolation functional carbon nanotubes (SH-CNTs) is presented and electrochemical measurements confirm that the Pt/SH-CNTs catalyst shows good durability and excellent ORR activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 15 publications
2
52
0
1
Order By: Relevance
“…[261][262][263][264][265] Wei et al found a strong interaction formed between Pt nanoparticles and thiolated carbon supports (Pt/SH-CNTs), resulting in markedly enhanced tolerance against Pt dissolution at high potentials. [261][262][263][264][265] Wei et al found a strong interaction formed between Pt nanoparticles and thiolated carbon supports (Pt/SH-CNTs), resulting in markedly enhanced tolerance against Pt dissolution at high potentials.…”
Section: View Article Onlinementioning
confidence: 99%
“…[261][262][263][264][265] Wei et al found a strong interaction formed between Pt nanoparticles and thiolated carbon supports (Pt/SH-CNTs), resulting in markedly enhanced tolerance against Pt dissolution at high potentials. [261][262][263][264][265] Wei et al found a strong interaction formed between Pt nanoparticles and thiolated carbon supports (Pt/SH-CNTs), resulting in markedly enhanced tolerance against Pt dissolution at high potentials.…”
Section: View Article Onlinementioning
confidence: 99%
“…For example, highly dispersed Pt nanoparticles supported on surface of thiolation functional carbon nanotubes, such as S-doped CNTs (SH-CNTs), CNTseC 6 H 6 eCH 2 eSH, CNTseCONHe(CH 2 ) 2 eSH, and CNTseCONHeC 6 H 6 eSH, were explored. 37,38 Furthermore, when some metal oxides such as NbTiO 2 and metal carbides were explored as the catalyst supports, strong interaction between catalyst and the support was also observed. 5,39…”
Section: Interaction Between Pt Catalysts and Supporting Materialsmentioning
confidence: 93%
“…研究 表明, 该催化剂的活性是同等条件下商业催化剂的三 倍, 同时其稳定性明显高于商业催化剂. Wei 和 Choi 等 [9,10] 在碳纳米管的骨架构型上引入巯基官能团, 并将 其作为催化剂的载体. 测试结果表明: 巯基官能团的修 饰使得催化剂在性能和稳定性上比商业催化剂有明显 的提高.…”
Section: 引言unclassified